Benin : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Benin. (IMF Staff Country Reports; Country Report ;, 2016)
This 2015 Article IV Consultation highlights that for the third consecutive year, Benin is expected to reach solid economic growth in 2015 at about 5 percent, despite recent headwinds from the economic slowdown in Nigeria-Benin's major trading partner. In 2016, increased public investment is expected to keep real GDP growth at about 5.2 percent, with inflation to remain subdued. The medium-term outlook is also positive overall, but subject to significant risks, including a further slowdown in Nigeria and delays of structural reforms that could weaken growth dynamics. Low debt levels help accommodate the government's ambitious plans to further scale-up investment over the medium term.